Some words used in scale insect names (Hemiptera: Sternorrhyncha: Coccoidea) - Williams, D. J. (Zootaxa, 2011)
In the Introduction to the present International Code of Zoological Nomenclature (International Commission on Zoological Nomenclature, 1999) (herein referred to as the Code), there is a remark that few zoologists today or in the future can have any knowledge of the Latin language although there is adherence to Latin grammar in the Code. The present Code, nevertheless, retains the requirement that Latin or latinized adjectival species-group names must always agree in gender with the generic name with which they are combined. Furthermore, Article 30 of the Code states that a genus-group name takes the gender given for that word in standard Latin dictionaries. Moreover, Article 39.1.2.a. states that a genus-group name that is, or ends in, a Greek word transliterated into Latin without change takes the gender given for that word in standard Greek dictionaries. However, such dictionaries may not be readily available to some people. The third edition of the Code, published in 1985, contained an appendix with recommendations on the formation of names that proved useful, but this section was omitted from the present edition of the Code.